Anti-nutritional metabolites and effect of treated Jatropha curcas kernel meal on rumen fermentation in vitro - Oskoueian, Ehsan; Abdullah, Norhani; Saad, Wan Zuhainis; Omar, Abdul Rahman; Puteh, Mansor; Ho, Yin Wan (Medwell Journals, 2011)
Jatropha curcas Linn. seed upon oil extraction resulted in a protein enriched byproduct called kernel meal. The presence of anti-nutritional metabolites in high levels renders the meal unsuitable as an animal feed. This research was carried out to determine the effects of physical and chemical treatments on the level of anti-nutritional metabolites present in the kernel meal. The effects of treated kernel meal on rumen microbial fermentation were evaluated in vitro. Proximate analysis of kernel meal obtained from J. curcas grown in Malaysia showed 61.8% crude protein, 9.7% NDF and 4.8% ADF. The anti-nutritional metabolites analyses showed high levels of total phenolic (3.9 mg g-1 DM), total saponin (1.9 g 100 g-1 DM), phytic acid (9.1%), trypsin inhibitors (34.2 mg g-1 DM), lectin activity (102.7 mg mL-1) and phorbolesters (3.0 mg g-1 DM). Combination of hydrothermal treatment, alkali and oxidizing agents alleviated the levels of anti-nutritional metabolites. Phenolic compounds, saponin and phorbolesters levels declined significantly (p<0.05) while the level of phytic acid did not decrease. Trypsin inhibitors and lectin activity were fully inactivated. The level of phorbolesters decreased by 76.7% in treatment with heat, 3% (w/w) NaOH and 10% (v/w) NaOCl. In vitro fermentation by rumen microbes showed significant (p<0.05) decrease in fermentation parameters when chemically treated kernel meal was used as substrates while physically treated kernel meal did not affect the fermentation parameters significantly.